2020
DOI: 10.12928/telkomnika.v18i2.14845
|View full text |Cite
|
Sign up to set email alerts
|

MPPT control of PV array based on PSO and adaptive controller

Abstract: In general, Photovoltaic (PV) array is not able to generate maximum power automatically, because some partial shading caused by trees, clouds, or buildings. Irradiation imperfections received by the PV array are overcome by applying maximum power point tracking (MPPT) to the output of the PV array. In order to overcome these partial shading problems, this system is employing particle swarm optimization (PSO) as MPPT method. It optimizes the output power of the solar PV array by Zeta converter. Output voltage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The suitable output voltage has been introduced by the buck-boost converter that ensures better transfer of the energy. The MPPT algorithm-based PSO is used to overcome these limitations and irradiation imperfection has been identified in 19 research. The adaptive PID is used to control the buck converter input voltage.…”
Section: Related Workmentioning
confidence: 99%
“…The suitable output voltage has been introduced by the buck-boost converter that ensures better transfer of the energy. The MPPT algorithm-based PSO is used to overcome these limitations and irradiation imperfection has been identified in 19 research. The adaptive PID is used to control the buck converter input voltage.…”
Section: Related Workmentioning
confidence: 99%
“…Mohanty et al devised the grey wolf optimization in order to gather the greatest amount of electricity from the PV systems while they were partially shaded. The findings of the simulation are analyzed and contrasted with those of the P&O and enhanced particle swarm optimization (PSO) methods [3], [6], [14], [26], [34], [70], [212], [214], [253], [254]. The results of the tests demonstrated that the grey wolf optimization works better than traditional algorithms in terms of tracking speed, ripple content, and extraction efficiency [255].…”
Section: Maximum Power Point Tracking (Mppt)mentioning
confidence: 99%
“…Further, the disadvantages such as partial shading was not allowed for generating maximum power. This algorithm with particle swarm optimization was utilized for overcoming these limitations as well as irradiations found in the study [58]. By the zeta converter, the solar photovoltaic output power was optimized, and with the step down device, some voltage would be regulated.…”
Section: Pso-ssa Algorithmmentioning
confidence: 99%